Ovulation induction techniques in women with polycystic ovary syndrome - Vyrides, Andreas A.; El Mahdi, Essam; Giannakou, Konstantinos (Frontiers in Medicine, 2022)
Anovulation is very common and has several different clinical manifestations, including amenorrhea, oligomenorrhea and abnormal uterine bleeding. Various mechanisms can cause anovulation. The clinical consequences and commonest chronic anovulatory disorder, polycystic ovary syndrome (PCOS), has a prevalence that ranges between 6% to 10% of the global population. While multiple causes can eventually result in PCOS, various methods have been described in the literature for its management, often without ascertaining the underlying cause. Ovulation Induction (OI) is a group of techniques that is used in women with PCOS who are looking to conceive and are unbale to do so with natural means. This narrative review presents a summary of the current evidence and available techniques for OI in women with PCOS, highlighting their performance and applicability.